PERSEPSI GURU PENDIDIKAN AGAMA KRISTEN INDONESIA TERHADAP PEMBELAJARAN ONLINE DI TENGAH COVID-19 DAN ERA INDUSTRI 4.0 - Jenri Ambarita; Ester Yuniati; Nurmiani Sinaga (Jurnal Shanan, 2020)
This study aims to describe the perceptions of Christian Religious Education teachers towards online learning carried out during the Covid -19 pandemic. PAK teachers' perceptions include aspects of ease of use, aspects of ease in building communication, aspects of its impact on teacher motivation in teaching, motivation to increase teacher creativity, and motivation of teachers to improve their skills in utilizing ICT. The research subjects were Indonesian PAK teachers who joined a telegram group which had 662 members. The data was collected by distributing questionnaires in the form of online questionnaires in the form of google forms. This research is a mixed research (mix method). The mixed research referred to in this paper is that the research data from the distribution of questionnaires will be presented in statistical form as quantitative data and the quantitative data presentation will be described as qualitative data. The results of this study are PAK teachers who are in areas with less smooth internet access, teachers who have never attended PPG or online learning workshops always feel that online learning is difficult to implement. Thus, Christian religious education teachers prefer to assign assignments to students. Christian Religious Education teachers who are in areas with smooth internet access, PAK teachers who have participated in PPG and online learning training activities feel that online learning is easy to implement, even PAK teachers have the view that the implementation of online learning provides positive motivation for teachers to be increasingly creative, increasingly skilled in utilizing ICT in learning.